TGF-β1 and TNF-α after red blood cell transfusion in colorectal cancer patients - Milasiene, V.; Stratilatovas, E.; Characiejus, D.; Kazbariene, B.; Norkiene, V. (Experimental Oncology, 2007)
Operations in patients with cancer are associated with blood transfusion to restore normal physiology. Blood transfusion can cause the immunomodulatory effect. There is lack of the literature data about influence of blood transfusion on the blood serum levels of cytokines TGF-β and TNF-α, though these cytokines are important in neoplasia development. The aim of our study was to estimate changes in the concentration of cytokines TGF-β1 and TNF-α in colorectal cancer patients’ peripheral blood after surgery and allogenic red blood cell transfusion. Methods: Venous blood of 64 patients with colorectal adenocarcinoma in stage III was tested before and after the surgery. Concentration of cytokines TGF-β1 and TNF-α was quantitatively measured by ELISA. Results: TGF-β1 and TNF-α concentration significantly increased in the group of transfused colorectal cancer patients (before operation: TGF-β 10.1 ± 1.3 ng/ml, TNF-α 20.9 ± 1.7 pg/ml and after operation and RBC transfusion: TGF-β 15.9 ± 1.7 ng/ml; TNF-α 27.0 ± 2.1 pg/ml). Statistical analysis has shown that serum levels of cytokines didn’t change significantly after surgery in non-transfused patients group. Conclusion: These results indicate that levels of multipotent cytokines TGF-β1 and TNF-α were elevated after red blood cell (RBC) transfusion in colorectal cancer patients. Операции больных онкологического профиля нередко сложные и сопровождаются переливанием крови для восстановления кровопотери. Данные литературы свидетельствуют о том, что переливание крови оказывает иммуномодулирующий эффект на организм пациентов. Однако существует недостаточно данных относительно влияния переливания крови на изменения концентраций цитокинов ТФР-β1 и ФНО-α, играющих важную роль в развитии опухолевой болезни. Цель: определение влияния переливания аллогенной эритроцитарной массы на изменения концентрации цитокинов ТФР-β1 и ФНО-α в периферической крови больных колоректальным раком после операции. Методы: концентрацию цитокинов ТФР-β1 и ФНО-α определяли методом ELISA у 64 больных раком толстой кишки III стадии до и после операции. I стадии до и после операции. Результаты: концентрация цитокинов ТФР-β1 и ФНО-α достоверно повышалась в периферической крови больных, которым после операции переливали аллогенную эритроцитарную массу (перед операцией: ТФР-β1 10,1 ± 1,3 ng/ml, ФНО-α 20,9 ± 1,7 pg/ml, после операции и переливания массы аллогенных эритроцитов: ТФР-β1 15,9 ± 1,7 ng/ml; ФНО-α 27,0 ± 2,1 pg/ml). Выводы: полученные результаты показали, что концентрация мультипотентных цитокинов ТФР-β1 и ФНО-α повысилась у больных колоректальным раком III стадии после переливания аллогенной эритроцитарной массы. I стадии после переливания аллогенной эритроцитарной массы.